2023
DOI: 10.1021/acscatal.3c02240
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Periodic Unsteady-State Water–Gas Shift Reaction on Highly Dispersed Cu-Loaded CeO2 Catalysts

Abstract: Kinetic analyses of Ce 4+ ↔ Ce 3+ redox and CO 2 /H 2 formation for the unsteady-state water−gas shift (WGS) reaction under periodic CO ↔ H 2 O feeds to Cu/CeO 2 catalysts are carried out by in situ/operando ultraviolet−vis and infrared studies at 350 °C. Under CO, the Ce 4+ −OH species are reduced to produce H 2 , CO 2 , and Ce 3+ −□ (oxygen vacancy). Under the subsequent feed of H 2 O, Ce 3+ −□ is reoxidized by H 2 O to yield H 2 and Ce 4+ −OH species. The rates of Ce 4+ reduction/ Ce 3+ reoxidation are clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The relative KM values with respect to the initial KM value (ΔKM) at 570 nm were also plotted versus NO feed time. Exposure of the preoxidized P(3)/CeO 2 to NO resulted in an increase in the absorption bands in the range of 500–800 nm, assignable to Ce 3+ -□. , The following stoichiometric scheme may account for this result and the IR results (Figure ) obtained under the same conditions. …”
Section: Resultsmentioning
confidence: 73%
“…The relative KM values with respect to the initial KM value (ΔKM) at 570 nm were also plotted versus NO feed time. Exposure of the preoxidized P(3)/CeO 2 to NO resulted in an increase in the absorption bands in the range of 500–800 nm, assignable to Ce 3+ -□. , The following stoichiometric scheme may account for this result and the IR results (Figure ) obtained under the same conditions. …”
Section: Resultsmentioning
confidence: 73%
“…Ceria-supported Cu (Cu/CeO 2 ) catalysts are among the most widely studied catalysts for the WGS reaction. Moreover, Manaka et al , and Bhan et al reported that a series of catalysts could be used for selective NH 3 formation from the NO–CO–H 2 O reaction, but the Cu/CeO 2 was the most effective one. To find the optimal catalyst for NH 3 synthesis using the NO–CO–H 2 O reaction, we compared the activity and selectivity of Cu­( x )/CeO 2 catalysts with different Cu loadings ( x = 2, 5, and 10 wt %) under the conditions of 0.1% NO, 0.5% CO, and 1% H 2 O (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, 29 the number of surface Cu sites (Cu dispersion) of Cu/CeO 2 catalysts (after H 2 reduction) was estimated using the N 2 O pulse method. The Cu dispersion decreased with an increasing Cu loading.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations